The Klone and I : a high-tech love story - Steel, Danielle (Delacorte Press, 1998)
A woman is torn between a man and his clone. The heroine is Stephanie who is being wooed by Peter, a bionic company director. When Peter is called away by work he sends Paul, his clone.